Potensi Bioremediasi Bakteri Indigenous dari Tempat Pembuangan Akhir dalam Mereduksi Metilmerkuri (HgCl₂) - Besse Khalidatunnisa (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
Heavy metal contamination, particularly mercury and its derivatives, represents a serious environmental issue with profound impacts on ecosystems and human health. Methylmercury (HgCl₂) is known to be highly toxic, persistent, and capable of bioaccumulating within the food chain. Bioremediation using indigenous bacteria offers an environmentally friendly and sustainable alternative approach. This study aimed to evaluate the diversity and adaptability of soil bacteria in response to mercury (HgCl₂) exposure at different concentrations. Soil samples were incubated with and without HgCl₂, and the number of bacterial strains as well as their growth tolerance were analyzed. The results showed that at day 0, 14 strains were identified in soil without HgCl₂ and 15 strains in soil with HgCl₂. After seven days of incubation, the number of strains slightly increased to 14 and 16 in soil without and with HgCl₂, respectively. Several new strains were detected on day 7, while some were no longer observed in either the control or treated samples. Tolerance assays revealed that certain isolates, such as K7, P1, and P10, were able to grow at mercury concentrations up to 30 ppm, whereas others could only survive at lower concentrations. These variations in growth patterns suggest different adaptive mechanisms, including the potential role of mercury reductase enzymes in detoxification. The findings highlight the ability of soil bacterial communities to survive and adapt to mercury contamination, underscoring their potential role in the bioremediation of heavy metal-polluted environments.